Study guides

☆☆

Q: What is the answer to 4 plus 6x equals 5 plus 3x plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x=4/3

Well lets see: 2y = 6x+8 y=3x+4 does not equal y=3x+6 So they are not the same.

To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.

9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4

9x2+6x-8 = 0 (3x+4)(3x-2) = 0 Therefore: x = -4/3 or x = 2/3

Related questions

x=4/3

6x-7 = 3x+5 6x = 3x+12 (subtracting -7) 3x=12 (subtracting 3x) x=4 (dividing by 3)

It is: 3x+4

Well lets see: 2y = 6x+8 y=3x+4 does not equal y=3x+6 So they are not the same.

To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.

6x + 8

9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4

It can be: y = 6x+4

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

6x + 4 = 3x + 19 3x + 4 = 19 3x = 15 x = 5 Check it. 30 + 4 = 15 + 19 It checks.

6x+4 factor: 2(3x+2)

34x + 72 is the answer to the equation 12 plus 6x-4 5 plus 2 3x-1.

People also asked